COVID-19 AND CORPORATE SOCIAL RESPONSIBILITY: EVIDENCE FROM NIGERIAN MICRO, SMALL AND MEDIUM ENTERPRISE (MSMEs) - Stephanie, M. (Economica, 2021)
The devastating impact of COVID-19 extends beyond health concerns; the coronavirus outbreak has rapidly transformed into an environmental, social and economic emergency. The global pandemic has prompted businesses to adopt innovative business models and re-strategize corporate social responsibility (CSR) in order to cope with the global challenges triggered by COVID-19. Micro, small, and medium-sized enterprises (MSMEs) are hit the hardest as they lack adequate resources to strive in these difficult times. This paper is a review article that uses secondary data to analysis COVID-19 pandemic and the CSR of MSMEs' in Nigeria. The study concludes that COVID-19 has a significant effect on MSMEs' CSR. Therefore, the study recommends that CSR projects should be compatible with government policies and plans to have a wider and even more sustainable effect. CSR engagement would be more fruitful if MSMEs embrace collective corporate social responsibility.